2020
DOI: 10.13004/kjnt.2020.16.e35
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Spinal Arachnoid Cyst as a Cause of Cauda Equina Syndrome in a Child

Abstract: Although spinal arachnoid cysts are relatively common findings observed incidentally in adults, they are much rarely reported in children. They are usually asymptomatic and are mainly located in the middle and lower thoracic regions. However, in rare circumstances, these cysts can cause mass effects that lead to neurologic symptoms. We report the rare case of a spinal extradural arachnoid cyst in a 12-year-old boy who showed signs and symptoms of cauda equina syndrome. Magnetic resonance imaging of the lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, it was always found that the SEACs had a pedicle linking with dura mater [ 4 , 28 ]. In our cases of total cyst excision, most cysts were round on both blind ends, and the cysts could be removed en bloc after wholly separating from the dura [ 9 , 13 , 28 , 29 ] ( Fig. 5 A and B).…”
Section: Discussionmentioning
confidence: 94%
“…However, it was always found that the SEACs had a pedicle linking with dura mater [ 4 , 28 ]. In our cases of total cyst excision, most cysts were round on both blind ends, and the cysts could be removed en bloc after wholly separating from the dura [ 9 , 13 , 28 , 29 ] ( Fig. 5 A and B).…”
Section: Discussionmentioning
confidence: 94%